PERSEPSI MASYARAKAT DESA SISARAHILI SUSUA TERHADAP BAHAYA ROKOK BAGI KESEHATAN - Novita Marlina Laia; Ujianhati Zega; Yohanna Theresia Venty Fau (Universitas Nias Raya, 2020)
Cigarettes contain substances that are harmful to health, the dangers range from mild to severe, such as coughing, bad breath to cancer. The purpose of this study was to determine how the perception of the community of Sisarahili Susua village on the dangers of smoking for health. This type of research is descriptive qualitative. This research was carried out from 07 May-14 June 2021, this research was carried out in Sisarahili Susua Village, Ulususua District. In this study, researchers took research samples of 6 informants. Researchers obtained data that the community of Sisarahili Susua village perceived that cigarettes were harmful to health, not only harmful to smokers but also to those around them who inhaled cigarette smoke. With the various perceptions that I have obtained, then I conclude that smoking is very dangerous for health, smoking cigarettes is the same as allowing disease to damage health, the reason that says that you can't stop because you are addicted is actually just an excuse because if there is an intention and a will then stop smoking can be stopped. Given the content of harmful chemicals in cigarettes, it is expected to be able to stop/reduce smoking so that our bodies avoid various effects of disease on health. My advice is for those of you who have smoked, both heavy, moderate and light smokers, let's reduce it if you stop, take care of your health, exercise and be regular in your diet so that health is ours together.